383 Evaluating the results of a mentoring scheme for medical students interested in pursuing a career in paediatrics. (17th August 2022) - Morris, Pippa; Yip, May; Natasha, G
Abstract : Aims: Over the past few years, there has been a decline in recruitment in paediatrics, with numerous campaigns commenced to encourage applications to the speciality, such as the #choosepaediatrics campaign. Whilst many medical students have an interest in paediatrics, exposure during medical school can be limited and variable - both within and between universities. In order to give medical students insight into paediatrics as a career, we devised the Cambridge University Paediatrics Society (CUPS) Buddy Scheme, a mentoring initiative. The aim of the scheme was to match medical students with paediatric trainees in the East of England region and provide them with opportunities to find out more about a career in paediatrics. Methods: We advertised the scheme through social media channels and bulletins throughout the East of England region, recruiting 34 mentors (ST1-8) and 39 medical student mentees (Year 1 to 6). Responses asked applicants to provide us with further information as to their sub-speciality interests, extra-curricular activities, placement location and their reasons for participating in the scheme. This enabled us to match mentors and mentees accordingly. Mentors and mentees attended briefing sessions where we outlined the aims of the pilot and suggestions of how to get the most from it. Mentors helped by providing careers advice, academic support and projects for students to get involved with. We collated anonymised feedback - both quantitative and qualitative - at the beginning, middle and end of the programme. Results: Analysis of the feedback yielded largely positive responses from mentors and mentees. All of the mentors believed the scheme was well organised and the majority have continued into the second year of the programme. 87% reported they had benefitted from mentoring, commenting on how they had improved their leadership, communication and teaching skills. Several highlighted the 'rewarding' nature of the experience. Constructive feedback suggested that having more mentees would be of benefit, due to the possibility of facilitating group sessions and sharing of ideas. Similarly, the mentees highlighted the success of the scheme, and the reassurance and encouragement it provided them with. Every student agreed that the scheme was well organised and that they were matched with a suitable mentor (n = 12). Mentees had a variety of experiences, from careers advice to research involvement. Some mentees found it difficult initially to contact their mentor, and thus for our second year of the programme we plan to have a mixing event to give the programme some more structure. Conclusion: The first year of the CUPS Buddy Scheme was a great success and has allowed medical students to gain valuable insight into paediatrics as a career pathway, whilst providing mentors transferable skills in supervision and leadership. We look forward to adapting and expanding this regional initiative to continue inspiring medical students to become paediatricians of the future.